Martin Luther King Jr. ’s "Our God Marches On" A Rhetorical Analysis of the Rhetoric Behind the Voting Rights Act of 1965 - Khan, Aaesha I. A (Journal of Social Science and Humanities, 2025)
The Voting Rights Act of 1965 left an ineffaceable inkblot in the history book of the United States of America, and especially that of African Americans. The signature of this historic act took shape after numerous battles against injustice. Several prominent African Americans raised their eloquent voices to lead these battles in dignity and self-respect. From these veterans, emerged Martin Luther King, Jr., a courageous and charismatic leader. No American remained indifferent to his great speeches, no matter what their religions or races. Martin Luther King, Jr., was the American moral voice of the 1950s and 1960s. His voice federalized the diverse groups into a melting pot, and made outspoken pleas of peace and justice everywhere. Great speeches travel through time and reach all generations because they have entered the immortal annals of history (Diop, 2024). In this paper, I will conduct a study on the oratory secrets behind King’s great speech that contributed to making a U.S. president sign the decisive Voting Rights Act in 1965. This study will explore the rhetorical devices King used in his speech “Our God Is Marching On”, which title has religious complexion, but which content is a tremendous learning experience. By analyzing King’s power of language, I will both probe the historical background of all the ballot-related protests that led to this speech, and I will investigate the mechanisms that made this speech an American literature masterpiece.